Fördjupad landskapsplanering i fjällnära skog - Landström, Petra (2022)
Fragmentation constitutes one of the biggest threats against biodiversity, and conservation efforts are increasing. Conservation efforts which are created at an international or national level may cause conflicts when it is time for the local implementation. This is a case study of Sorsele municipality and takes its starting point in the Forest investigations’ suggestion to protect another 525 000 hectares in proximity to the mountain forest border (MFB). I have performed a GIS-analysis of high conservation value forest (HCVF) within Sorsele municipality with the purpose to illustrate the distribution of these regarding forest owner category, forest land area, above and below MFB, and spruce or pine dominated forest land. I have also conducted semi-structured interviews with 30 private forest owners within Sorsele municipality with the purpose to raise the perspectives of private forest owners on the suggestion of the Forest investigation, formal protection, compensation, and alternative forest management as an alternative to clear-cut forestry. My GIS-analysis showed that the majority of the HCVF in Sorsele municipality are concentrated above the MFB for all owner categories. Very few of the HCVF were dominated by pine, which mirrors the landscape characteristics. To reduce the risk of conflicts arising from conservation efforts, my interview analysis indicates that, beyond substance, both processes and relations are important factors to consider. The same conflict can be experienced in various ways among different individuals. Some experience the conflict just as a conflict while another may experience it as an underlying conflict and others may experience it as an identity-based/deep-rooted conflict. These three levels of conflict are commonly found in conflicts arising from conservation initiatives. The result of this study emphasizes the importance of involving local inhabitants in the process of formal protection. It also calls for flexible, individually tailored solutions along with nature conservation agreements as an effective tool towards finding a balance between forestry, nature conservation, and other land-use.